Implementasi Etika Bisnis Islam sebagai Strategi Bersaing pada PT Mahesa Energi Persada Jakarta - Ii Hikmat Ismail; Mawardi Nur (Neolectura, 2021)
This study aims to analyze the application of Islamic business ethics at PT Mahesa Energi Persada Jakarta as a competitive strategy. Given the rampant unhealthy competition carried out by companies engaged in the solar sector. This type of research uses qualitative research. The type of data used is primary data obtained by observation, interviews and documentation, secondary data obtained from books and journals. The data analysis technique of this research is descriptive qualitative. The results of this study are the implementation of Islamic business ethics by PT Mahesa Energi Persada by applying the principles of Islamic business ethics including the Principle of Unity, the Principle of Balance, the Principle of Free Will, the Principle of Responsibility and the Principle of Virtue. It can be concluded that PT Mahesa has implemented Islamic business ethics as competitive advantage. The suggestion from the author is that PT Mahesa Energi Persada is expected to be consistent in applying the principles of Islamic business ethics, increasing the quantity and quality of human resource management and increasing the company's capital by looking for investors.